Alerting, orienting, and executive control in intellectually gifted children. Issue 8 (19th July 2021) - Aubry, Alexandre; Bourdin, Béatrice
Abstract: Introduction: Intellectually gifted children have higher performance in many domains of attention than intellectually average children. However, these empirical findings are not consistent in the literature. Few studies investigated the characteristics of alerting, orienting, and executive control networks in intellectually gifted children. The aim of our study was to investigate their characteristics of attentional abilities compared to intellectually average children. Method: Fifty‐five intellectually gifted children (age range 8–14 years old) were compared to 55 intellectually average children (age range 8–14 years old) using the Attention Network Test (ANT) to assess these three attentional constructs. Results: Intellectually gifted children made fewer errors than intellectually average children in the processing of the ANT. In terms of attention network scores, they also outperformed intellectually average children in executive control only. Conclusion: Intellectually gifted children do not differ from intellectual average children in terms of the speed of processing in a speeded task such as ANT, but they stand out in terms of accuracy of processing. Intellectually gifted children have better ability to focus volitionally in order to solve a simple perceptual conflict than intellectually average children. Abstract : The aim of this study was to investigate the characteristics of three attentional networks in intellectually gifted children. The findings show the intellectually gifted children have better ability to focus volitionally in order to solve a simple perceptual conflict than intellectually average children.